The Role of Pesantren Culture in Bullying Prevention: A Systematic Review - Nikmatul Khabibah; Suhadianto; Noviekayati (PT. Caesarindo Triloka Persada, 2026)
Although Islamic boarding schools (pesantren) emphasize character education through moral values, religious practices, and exemplary role models, bullying continues to occur within these institutions. Existing studies have highlighted the potential of pesantren culture in fostering positive student behavior; however, empirical evidence regarding its effectiveness in preventing bullying remains fragmented and is largely dominated by qualitative research. This study aims to synthesize the available empirical evidence on the effectiveness of the pesantren cultural approach in preventing bullying among santri through a Systematic Literature Review (SLR). Following the PRISMA 2020 guidelines, literature published between 2015 and 2025 was systematically identified from Google Scholar and the Directory of Open Access Journals (DOAJ). Of the 200 records initially identified, 10 studies met the inclusion criteria after screening, quality appraisal using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, and full-text review. The synthesis indicates that pesantren culture contributes to bullying prevention by strengthening empathy, moral awareness, emotional regulation, and a positive social climate through value internalization, exemplary leadership, mentoring systems, religious practices, and collaborative conflict resolution. However, current evidence is predominantly derived from qualitative studies using indirect indicators of bullying prevention, limiting robust conclusions regarding causal effectiveness. This review contributes to the literature by consolidating fragmented evidence on the role of pesantren culture in bullying prevention while highlighting the need for rigorous quantitative and longitudinal studies that operationalize pesantren culture as a measurable construct and examine its direct influence on bullying behavior among santri.